On-Line Solid-Phase Extraction of Fluoroquinolone Residues from Milk with Enrofloxacin-Imprinted Monolithic Column - Lv, Yun-Kai; Jia, Cui-Ling; Wang, Xiao-Hu; Zhang, Li-Wei (Asian Journal of Chemistry, 2012)
On-line solid-phase extraction method was developed by enrofloxacin-imprinted monolithic column (monolithic MIP) coupling with reversed-phase high-performance liquid chromatography for preconcentration and separation of fluoroquinolone residues in milk. The monolithic MIP was prepared by in situ polymerization in a stainless-steel chromatographic column. An enrichment factor of 6.70 along with a good sample clean-up effect was obtained. High recoveries for three fluoroquinolones such as enrofloxacin, ciprofloxacin and norfloxacin were achieved, which was in the range of 82.0-94.0 % with precision lower than 5.6 %. The limit of detection and limit of quantitation of the proposed method were in a range of 4.31-7.62 μg/kg and 14.37- 25.40 μg/kg, respectively. The proposed method was successfully applied to on-line preconcentration, separation and determination of the fluoroquinolones in the milk sample.